Analysis of Antioxidant Activity of Ethanol Extracts of Cocoa Fruit Peel (Theobroma cacao L.) and Arabica Coffee Fruit Peel (Coffee arabica L.) with Maceration and Reflux Extraction Method - Indah Indah; Dina Lestari; Shintia Puja Lasenda; Rina S E Sitindaon (Journal of Food and Pharmaceutical Sciences, 2025)
Cocoa and coffee are well-known commodities in the world, including Indonesia. The seeds of cocoa and coffee are often utilized. Cocoa beans are usually processed into chocolate products, while coffee becomes a beverage product. Utilization of cocoa and coffee beans, and fruits produces waste, namely the skin. The more cocoa and coffee production, the more fruit skin waste. One of the efforts to utilize fruit skin waste is by extracting the antioxidant content from it. The choice of extraction method is important to produce extracts with the maximum amount of extract. Therefore, a study was conducted on the comparison of maceration and reflux extraction methods in determining the highest level of antioxidant activity. Cocoa and coffee fruit peels were extracted using ethanol, and the extracts were tested for antioxidant activity using DPPH with ascorbic acid as a positive control using UV-Vis spectrophotometry. The results of the antioxidant activity test conducted with the DPPH method showed that the IC50 value of macerated cocoa fruit peel extract was 5.440 ppm, and coffee was 62.99 ppm the reflux extract of cocoa fruit peel was 4.999 ppm, and coffee was 61.68 ppm. This shows that the maceration and reflux methods of cocoa can be categorized as very strong antioxidants and strong arabica coffee. from the two extraction methods of this study, it is concluded that there is no significant difference between maceration and reflux.